2016
DOI: 10.15740/has/ijpp/9.1/158-161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biorationals against the thrips, Scirtothrips dorsalis Hood infesting chilli

Abstract: The present investigation was carried out to test the efficacy of biorationals against thrips, Scirtothrips dorsalis Hood on chilli. Field experiments were conducted at farmers holding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…One application of emamectin benzoate/chlorfenapyr along with some plant products was found to be much better in suppression of leaf curling intensity in chilli (Chakraborti et al 2015). Effectiveness of emamectin benzoate in the present study was also supported by study conducted by Ravikumar et al (2016), where they reported that emamectin benzoate 5 sg @0.4 g per litre of water was very effective against chilli thrips, S. dorsalis. A study conducted on efficacy of biorational insecticides against chilli thrips, S. dorsalis by Aristizábal et al (2017) was also consistent with present study where consistent use of spinosad was the most effective treatment against chilli thrips.…”
Section: Resultssupporting
confidence: 85%
“…One application of emamectin benzoate/chlorfenapyr along with some plant products was found to be much better in suppression of leaf curling intensity in chilli (Chakraborti et al 2015). Effectiveness of emamectin benzoate in the present study was also supported by study conducted by Ravikumar et al (2016), where they reported that emamectin benzoate 5 sg @0.4 g per litre of water was very effective against chilli thrips, S. dorsalis. A study conducted on efficacy of biorational insecticides against chilli thrips, S. dorsalis by Aristizábal et al (2017) was also consistent with present study where consistent use of spinosad was the most effective treatment against chilli thrips.…”
Section: Resultssupporting
confidence: 85%
“…Imidacloprid is activity on various sucking pests, containing thrips and wide variety insecticide known for pest (McKenzie et al, 2015). A study worked on effectiveness of biorational insecticides on chilli thrips and S. dorsalis (Ravikumar et al, 2016), where they reported that, emamectin benzoate 5 sg @0.4 g per liter was very successful against chilli thrips and S. dorsalis.…”
Section: Resultsmentioning
confidence: 99%
“…Sumitha et al (2008) investigated that population of Scirtothrips dorsalis was controlled effectively by fipronil 5 SC @ 0.01%. Ravikumar et al (2016) observed that maximum yield (30050 kg ha -1 ) was recorded by spray of Spinosad 45 SC @ 0.01 % against thrips.…”
Section: Percent Mortality Of Thrips 72 Hours After Spray During 2022mentioning
confidence: 93%